Effect of APOE Gene on White Matter Integrity : A DTI Study in Healthy Elderly Adults - Tato Fernandez, Claudia (My University, 2023)
The aim of this project was to examine how APOE4 allele influences white matter integrity in cognitively unimpaired elderly adults at different genetic risk of sporadic Alzheimer’s disease. 57 subjects recruited through the local Auria Biobank (Turku, Finland) were included in this experimental study (Group 1: APOE4/4, N = 16; Group 2: APOE4/3, N = 20; Group 3: APOE3/3, N = 21). Mean age of the cohort was 67.50. All subjects underwent magnetic resonance imaging (MRI) protocol and positron emission tomography imaging (PET) with a tracer targeted against amyloid-β (Aβ) deposition (11C-PIB). MRI protocol consisted in T1-weighted, T2-weighted, FLAIR and DTI sequences, including two non- diffusion-weighted (b = 0) images with opposing phase-encoding directions. DTI-derived metrics fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AxD), radial diffusivity (RD) and mode of anisotropy (MO) were estimated in voxel-wise analysis and in selected regions of interest (genu of corpus callosum, cingulate cortex adjacent to hippocampus, cingulate cortex adjacent to cingulate gyrus, fornix and uncinate fasciculus). A voxel-weighted average of these regions was calculated and subsequently correlated with white matter hyperintensities and Aβ deposition. Regional data was compared between groups using FDR-corrected ANCOVA and whole-brain analysis was done with TFCE-corrected independent samples t-test between APOE4/4 and APOE3/3 carriers. We hypothesized that APOE4 carriers would exhibit more white matter pathology than APOE3/3, in a gene-dose dependent fashion. However, in the present study, no significant differences between the APOE4 gene-dose groups were found in the selected regions of interest, nor in whole-brain analysis (all p > 0.05 after correction for multiple comparisons). APOE4/4 showed a trend towards higher mean and axial diffusivity in the cingulum, uncinate fasciculus and genu of corpus callosum, which was statistically significant after applying a more liberal threshold in exploratory analysis. A positive correlation was found between axial diffusivity and Aβ deposition only in APOE4/4 (R = 0.54, p = 0.03), but not in the whole sample (R = 0.19, p = 0.17). The reverse trend towards a negative correlation was found in APOE3/3 (R = 0.43, p = 0.066). In conclusion, although this study was not able to reveal a significant relationship between APOE4 gene dose and disruption of white matter integrity, our findings suggest there is a trend towards increased diffusivity in APOE4/4, which correlates with amyloid-β deposition. This trend was noticeable even in our relatively small dataset.
Keywords: Alzheimer’s disease, APOE, ApolipoproteinE, DTI, diffusion tensor imaging, TBSS, myelin, fractional anisotropy, FA, mean diffusivity, MD, axial diffusivity, AxD, radial diffusivity, RD, PET, 11C-PIB